2001
DOI: 10.1046/j.1471-1842.2001.d01-16.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical illustration: from caves to cyberspace‡

Abstract: The human body has been depicted in ancient cave‐paintings, in primitively sculpted figures, and through all the ages in various forms of artistic expression. The earliest medical texts were descriptive but not illustrated. Later, as it became clear that knowledge of the human body and all its systems was essential to the practice of healing, texts were accompanied by illustrations which became an integral part of the teaching process. The illustrators included artists, whose interest was primarily artistic, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…However preparation of anatomical illustrations was yet to develop as an independent profession. With the beginning of 20th century, opportunities started to grow permitted by social and cultural changes as well as technological advances (Tsafrir and Ohry, ). Such favorable circumstances paved the way for the emergence of professional anatomical illustrators, who made significant contributions to the subject in the last century.…”
Section: Modern Times (1900 Ad To Present Day)mentioning
confidence: 99%
See 1 more Smart Citation
“…However preparation of anatomical illustrations was yet to develop as an independent profession. With the beginning of 20th century, opportunities started to grow permitted by social and cultural changes as well as technological advances (Tsafrir and Ohry, ). Such favorable circumstances paved the way for the emergence of professional anatomical illustrators, who made significant contributions to the subject in the last century.…”
Section: Modern Times (1900 Ad To Present Day)mentioning
confidence: 99%
“…Later on the acceptance of human dissection as a scientific method to advance understanding of anatomical structure led to the development of anatomical illustration (Calkins et al, ). Over the years pictorial representation of anatomy has evolved considerably with the artistic expression varying across all the ages (Tsafrir and Ohry, ). This review article highlights the works of esteemed anatomists in a chronological pattern in an attempt to outline the sequential manner of the process of evolution of anatomical illustrations.…”
Section: Introductionmentioning
confidence: 99%
“…The Visible Human Project alone cost US$1.4 million to acquire and assemble spatial data of human organs (Garg et al, ). Publishing companies and educational institutions are constantly producing new educational illustrations with the goal of increasing the quality and quantity of resources available to students (Tsafrir and Ohry, ). In a recent gathering of medical education experts, a major concern was that the advancement of sophisticated teaching resources was outpacing the understanding of how they should be developed and used (AAMC, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Visible Human Project was a significant collaborative effort among anatomists to produce a web-based learning tool with detailed 3D images of cross-section and whole-body representations derived from MRI and CT scans (Spitzer and Whitlock, 1998;Tsafrir and Ohry, 2001). Several studies have shown improved learning outcomes when computer-aided instruction containing 2D and 3D images were used to complement lectures and dissection (Stanford et al, 1994;McNulty et al, 2004;Venail et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In support of an electronic curriculum, health sciences educators and administrators are becoming aware of the need for digital repositories to catalog, store and provide access to digital images and other digital learning objects (Fleiszer, Posel, & Steacy, 2004). Tsafrir and Ohry, among others, note that technology has continually changed the way in which images are captured and delivered and that the increasing “accumulation of pictorial material has posed considerable problems of storage, cataloging, retrieval, display and dissemination of the information”(Tsafrir & Ohry, 2001, p. 99). Other researchers, such as Attig, Copeland, and Pelikan (2004), have examined the challenges of creating metadata for a library of digitized images.…”
Section: Introductionmentioning
confidence: 99%